Strategi Manajemen Kurikulum untuk Meningkatkan Kualitas Lulusan di SMK Negeri 1 Sungai Tabuk - Gilang Dwi Kurniawan; Marini, Marini; Resyadilla Azkia; Rida Maulidia; Ahmad Suriansyah; Ratna Purwanti (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This article aims to describe the curriculum management strategies implemented at SMKN 1 Sungai Tabuk to improve the quality of graduates in alignment with the demands of the workforce. This research employs a descriptive qualitative method with data triangulation techniques through interviews, observation, and documentation. The findings reveal that curriculum management is carried out systematically through planning, organization, implementation, and evaluation. In the planning phase, the school develops annual and semester programs, Learning Objectives Flow (ATP), and teaching modules aligned with the needs of the Business and Industrial World (DUDI). The organization of the curriculum involves teacher participation in ongoing training, professional learning communities, subject teacher working groups (MGMP), and industry internships. Curriculum implementation is supported by strategic partnerships through fieldwork practice programs and graduate placement facilitated by the School Job Placement Unit (BKK). Curriculum evaluation is conducted collaboratively by the curriculum development team and various school program teams, taking into account feedback from teachers, students, and industry partners. However, several challenges remain, including limited teacher innovation in lesson planning, inadequate facilities, and insufficient mastery of the Merdeka Curriculum approach. This study recommends enhancing teacher capacity, improving learning infrastructure, and strengthening collaboration among stakeholders in curriculum management to produce more competent and industry-ready graduates.